STUDENTS’ PERCEPTION TOWARD MEMRISE APPLICATION AS MEDIA IN LEARNING VOCABULARY - Aulia Putri; Mimi Nova Windari Simanjuntak (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
The objective of this study is to find out and describe about students’ perception toward Memrise application as Media in Learning Vocabulary at seventh grade school SMP N 62 BATAM. The participants are students at VII grade of SMP N 62 BATAM. This research is prepared based on field data using Qualitative research. Method data collection in this research was conducted by using questionnaire and interview. As for the data analysis technique, the researcher used data reduction, data display, and conclusion. The finding is students’ perception toward Memrise application as Media in Learning Vocabulary get positive perception and can help improve vocabulary mastery for English lesson. Memrise application gives so many benefits for the students. Beside this application easily to operate, Memrise application also has interesting feature. The lesson material from Memrise application is easy to understand by students and through Memrise application, students have more spirit to learn vocabulary in English and their phone is not only for playing game but they can use it for study.